Training load and performance impairments in professional cyclists during COVID-19 lockdown - Muriel, X.; Courel-Ibanez, J.; Cerezuela-Espejo, V.; Pallarés, J. G. (International Journal of Sports Physiology and Performance, 2020)
Purpose: The COVID-19 outbreak has challenged professional athletes` training and competition routines in a way not seen before. This report aims to inform about the changes in training volume and intensity distribution and their effects on functional performance due to a 7-week home-confinement period in professional road cyclists from a Union Cycliste Internationale Pro Team. Methods: A total of 18 male professional cyclists (mean [SD] age=24.9 [2.8] y, body mass=66.5 [5.6] kg, maximal aerobic power?=?449 [39] W; 6.8 [0.6] W/kg) were monitored during the 10 weeks before the lockdown (outdoor cycling) and the 7-week lockdown (indoor cycling turbo trainer). Data from the mean maximal power output (in watts per kilogram) produced during the best 5-minute and best 20-minute records and the training intensity distributions (weekly volumes at power-based training zones) were collected from WKO5 software. Results: Total training volume decreased 33.9% during the lockdown (P<.01). Weekly volumes by standardized zones (Z1 to Z6) declined between 25.8% and 52.2% (effect size from 0.83 to 1.57), except for Z2 (P=.38). There were large reductions in best 5-minute and best 20-minute performance (effect size>1.36; P<.001) with losses between 1% and 19% in all the cyclists. Conclusions: Total indoor volumes of 12 hours per week, with 6 hours per week at low intensity (Z1 and Z2) and 2 hours per week at high intensity over the threshold (Z5 and Z6), were insufficient to maintain performance in elite road cyclists during the COVID-19 lockdown. Such performance declines should be considered to enable a safe and effective return to competition.